ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI MEDIASI PADA PERUSAHAAN DEVELOPMENT PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA 2007 - 2010 - Lies Indriyatni (STIE Pelita Nusantara Semarang, 2012)
The aims of this research is to know factors which influence company value with modal structure as the mediation on Development Property companies that are listed in Indonesia Stock Exchange. Analysis method which will be used is Quantitative method by using Path Analysis with the help of SPSS ver.17. The results gained from the research showed that the Profitability factor didn’t have any influence on company value since the significant value is just 0.276, bigger than 0.05 and t-count value 1.110, less than t-table(2.045). Meanwhile, other factors like assets structure, Sales growth and Financial risk influenced the company significantly. It can be shown on t-count value from each of those factors (6.234, 2.351, and 2.461) which were bigger than t-table on alpha level 5% which is 2.045. By including Modal Structure as mediation variable, we gained a result that high modal structure is able to strengthen or moderate the influence of those factors on company values. From the research results, it is suggested that ; Firstly, If the company’s goal is improving the company value then the optimum modal structure deciding process has to be strived correctly. Secondly, Some factors, like Assets structure, Sales growth and Financial risk, are important to be paid attention on company values improvement efforts. And Lastly, for stockholder’s wealth, company value improvement is more important than profit improvement.